Inteligência emocional em projetos: uma conexão entre o líder e a equipe - Cavaletti, Samir (2023)
Leading is interacting with human groups and since there are no human interactions without the presence of emotions, it is expected that an emotionally satisfying environment comes from the interaction between leader and subordinates. Although it should be expected that this approach comes first from the leader, the interaction with the team needs to mirror this behavior, thus creating a better environment and a culture of acceptance, which reflects in greater project success. Therefore, a leader can be more effective when looking to engage and motivate his/her team in support of their projects. For this, it is advisable for the leader to emotionally interact with subordinates, allowing this exchange. In this context, we understand that the transformational leadership style is an important factor in explaining the formation of a team. However, the practice of transformational leadership requires empathy to understand the emotions of those who are led, and motivation, to influence engagement. In this way, this thesis aims to identify how much the emotional intelligence of the team can interact with the leader for the success of the project. In this context, to first recognize the importance of the leader in the process, especially the transformational leader within the project as an inspiring and motivating leader of the team, and to better understand this interaction, in the first part of the study we identified through a systematic literature review how emotional intelligence impacts transformational leadership. In the second part of the study, we sought to explore the interaction between transformational leadership in a project and the emotional intelligence of the group. To understand how they interact we measured within the project teams how much the emotional intelligence of the group can support a transformational leader, even if this is narcissistic, to achieve success in a project. Finally, a tool was developed to support organizations in assembling and developing emotionally integrated project teams so that this knowledge can be disseminated within organizations and have a more objective practical contribution. Leadership, within a project, is a particular vision of organizational leadership, where we consider the additional constraints such as time limitations, newly formed teams, and changing environments. In this context, the leader needs to accelerate the process of engagement and the creation of mutual trust. We looked to explain the concepts of emotional intelligence and transformational leadership as capabilities of the leader and the team that can strengthen relationships in this direction. As a theoretical contribution, this work reinforces previous research on the importance of emotional intelligence for the formation of project teams, demonstrating that the interaction of the transformational leader in a project with his team creates a welcoming environment, capable of accepting different points of view, which is beneficial for the project. As a practical contribution, this work will deliver a tool built on a scientific basis, to aid project managers and HR managers in the choice and evaluation of team members to identify teams with the best potential for success, allowing them to better establish training and integration activities.